2010
DOI: 10.1002/mrc.2635
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives in the PAW/GIPAW approach: JP-O-Si coupling constants, antisymmetric parts of shift tensors and NQR predictions

Abstract: In 2001, Pickard and Mauri implemented the gauge including projected augmented wave (GIPAW) protocol for first-principles calculations of NMR parameters using periodic boundary conditions (chemical shift anisotropy and electric field gradient tensors). In this paper, three potentially interesting perspectives in connection with PAW/GIPAW in solid-state NMR and pure nuclear quadrupole resonance (NQR) are presented: (i) the calculation of J coupling tensors in inorganic solids; (ii) the calculation of the antisy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 129 publications
(105 reference statements)
2
52
0
Order By: Relevance
“…The PBE generalised gradient approximation was used and the valence electrons were described by norm conserving pseudopotentials [72] 43 Ca and 25 Mg, the quadrupolar parameters C Q and η were also analysed. [38] It should be noted that based on previous studies and our own experience, the error on calculated 1 H and 31 P isotropic chemical shifts is estimated at ~0.4 [77] and 0.7 ppm, [78] respectively, whereas it is ~3 to 5 ppm on 43 Ca and 25 Mg isotropic chemical shifts, and ~0.5 to 2 MHz on 43 Ca and 25 Mg C Q values, [37,39] respectively. The four Ca(I) ions in the unit cell are usually referred to as "columnar calcium sites", because they form single atomic columns perpendicular to the basal plane.…”
Section: Dft Calculations Of the Nmr Parametersmentioning
confidence: 99%
“…The PBE generalised gradient approximation was used and the valence electrons were described by norm conserving pseudopotentials [72] 43 Ca and 25 Mg, the quadrupolar parameters C Q and η were also analysed. [38] It should be noted that based on previous studies and our own experience, the error on calculated 1 H and 31 P isotropic chemical shifts is estimated at ~0.4 [77] and 0.7 ppm, [78] respectively, whereas it is ~3 to 5 ppm on 43 Ca and 25 Mg isotropic chemical shifts, and ~0.5 to 2 MHz on 43 Ca and 25 Mg C Q values, [37,39] respectively. The four Ca(I) ions in the unit cell are usually referred to as "columnar calcium sites", because they form single atomic columns perpendicular to the basal plane.…”
Section: Dft Calculations Of the Nmr Parametersmentioning
confidence: 99%
“…Appropriate k-point meshes for crystalline models and optimize forces to lower than to 5 meV/Å were chosen. 29 Si and 31 P chemical shifts were calibrated based on the experimentally measured chemical shifts [60] for AIV-SiP 2 O 7 , [61] HexI-SiP 2 O 7 , [62] and Si 5 O(PO 4 ) 6 [63] structures. For those we chose an energy cutoff of 600 eV and found the 29 Si NMR chemical shifts converged to better than 0.2 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar vein, care must be taken in comparing J involving different species. For example, 31 P– 17 O couplings are typically larger than 29 Si– 17 O couplings 11. Part of this difference is due to the fact that γ P ≈ 2γ Si , and it would be reasonable to expect that calculated errors in J for 31 P‐ 17 O couplings would be twice as large as for 29 Si– 17 O couplings.…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…Experimentally only the total tensor can be measured, however, the contributions (sometime called the Ramsey terms) can be useful in interpreting the observed J . Quantum chemical studies have shown that several general observations can be made,25 and so far these have been found to also apply to solid‐state systems:8–11 the DSO term is generally very small; the SD term is usually small, but can play a significant role certain couplings—e.g. those involving 19 F; for one bond couplings the PSO and FC terms are dominant; and for longer range couplings usually the FC is the dominant mechanism.…”
Section: Experimental Considerationsmentioning
confidence: 99%
See 1 more Smart Citation